Understanding the drivers of advertising elements through different media and generations in building brand equity: a neuromarketing approach - Ganto Novialdi; Sri Rahayu Hijrah Hati (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study was designed to measure the visual attention of each generation towards the advertising elements with the Neuromarketing approach. By using the eye tracker device in a centralized location test (CLT), in this study, we compare advertising element stimulus along with three moderators: print, digital and social media to respondents from Generation X, Generation Y, and Generation Z. The research result indicate that Generation X is the most adaptive generation and emphasizes visual elements in viewing advertisements, regardless of the type of media. This can be seen from the high fixation duration in all media types. Generation Y did not significantly differ in the duration of fixation on the three media types but seemed to be more concerned with textual elements than other generations. Meanwhile, Generation Z does not prefer any media and advertising elements based on a temporary fixation duration when viewing advertisements.